Potential evapotranspiration estimates for northeast Brazil using GOES-8 data Estimativa de evapotranspiração potencial para o nordeste do Brazil utilizando dados do GOES-8 - Eduardo J. de Brito Bastos; Jaidete M. de Souza; Tantravahi V. Ramana Rao (Revista Brasileira de Engenharia Agrícola e Ambiental)
In this study, an empirical method proposed by Caselles et al. (1992a) is utilized to determine the potential evapotranspiration (ETP) on a regional scale. This method uses the global solar radiation data retrieved by the global radiation model GL1.0, which in turn utilizes data from the visible channel of the GOES-8 satellite. This method is applied to the northeast region of Brazil, using daily and monthly climatological data as the ground truth information to estimate the ETP and the estimated daily ETP data for September, 1997. The methodology involved three steps: 1) to perform a spatial regionalization of the ETP using the method of Ward, which is available in the Statistical Package for the Social Sciences (SPSS); 2) to obtain the correlation between the ETP as estimated by the methods of Jensen & Haise (1963) - MJH, Caselles (1992a) - MCA, and the Penman's combined method (1948) - MCP; 3) to test the sensibility of the empirical formulations proposed and to assess the estimates using the satellite-based global solar radiation provided by the GL1.0 model. The spatial regionalization shows two distinct regions in the Northeastern Brazil. The MCA yielded better results than the MJH. The ETP estimates using satellite data were satisfactory, showing a maximum error of 20% when compared with the ground truth data. Neste trabalho foi utilizado o método empírico proposto por Caselles et al. (1992a) para determinar a evapotranspiração potencial (ETP) em escala regional. O método utiliza dados de radiação solar global obtidos a partir de um modelo de estimativa da radiação solar global (GL 1.0), que utiliza imagens do canal visível do satélite GOES-8. O método é aplicado no Nordeste do Brasil, utilizando como verdade terrestre dados climatológicos diários e mensais para estimar ETP e dados diários estimados de ETP para setembro de 1997. A metodologia contempla três etapas: 1) regionalização espacial da ETP obtida pelo método de WARD, disponível no software SPSS (Statistical Package for the Social Sciences); 2) correlação entre os valores de ETP estimados pelo método de Jensen & Haise (1963) MJH, Caselles et al. (1992a) MCA e pelo método combinado de Penman (1948) MCP, respectivamente; e, 3) teste de sensibilidade das formulações empíricas utilizadas e validação dos resultados. A regionalização espacial mostrou duas regiões distintas no Nordeste do Brasil. O MCA apresentou melhores resultados do que o MJH e a ETP estimada, usando dados de satélite, apresentou um erro máximo de 20%, quando comparada com a verdade terrestre.